Molecular Docking and Dynamic Simulation of Erythrina fusca Lour Chemical Compounds Targeting VEGFR-2 Receptor for Anti-Liver Cancer Activity - Maharani, Dila Aulia; Adelina, Rosa; Aini, Anggun Qurrota; Supandi, Supandi (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Liver cancer is a serious health concern characterized by abnormal cell growth, but currently, available treatment options are limited, suggesting the need for a new therapeutic method. Therefore, this research aimed to investigate the potential of chemical compounds obtained from the cangkring plant (Erythrina fusca) as anti-liver cancer agents targeting Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2). The investigation was conducted in silico through molecular docking and dynamic method. Molecular docking was performed using AutoDock Tools, followed by visualization with Biovia Discovery Studio. Additionally, molecular dynamics simulation was conducted using GROMACS software and visualized with Grace. A total of 36 chemical compounds from E. fusca were used as ligands for molecular docking. The results showed that Isobavachalcone (ISB) was the most effective test compound with a binding energy of -11.45 kcal/mol, compared to the positive control Sorafenib with a value of - 11.51 kcal/mol. In this context, hydrogen bonding, as well as hydrophobic, electrostatic, and unfavorable molecular interactions were identified. Moreover, molecular dynamics simulation provided RMSD, RMSF, Radius of Gyration (Rg), and hydrogen bond parameters. Analysis of these parameters further confirmed the superior stability of ISB in binding to VEGFR-2, suggesting the potential to suppress angiogenesis by blocking the receptor.